Maternal, Newborn, and Child Survival (MNCS) Training Package for Frontline Health Workers in Resource-Limited Settings - Maya Fehling; Brett Nelson; Roy Ahn; Melody Eckardt; Margaret Tiernan; Genevieve Purcell; Thomas Burke (Association of American Medical Colleges, 2014)
Abstract Introduction The Maternal, Newborn, and Child Survival (MNCS) Training Package was developed to train frontline health workers (FHWs) who take care of pregnant mothers, newborns, and children in rural sub-Saharan Africa. These informal health care workers are often nonliterate and live in areas where health care services and skilled birth attendants are a scarce resource. Our training focuses on the recognition of danger signs so that sick mothers and children can be referred on time. We also train simple life-saving skills to the FHWs in the case of emergencies. In addition to training, setting appropriate reusable equipment and supplies are provided directly to trainees since supply lines are frequently disrupted or nonexistent. Methods A multi-modal needs assessment was first conducted to develop a best-evidence package comprised of targeted training, and pictorial checklists, as well as reusable equipment and commodities. Implementation utilized a training-of-trainers model. Program effectiveness was assessed through knowledge assessments, objective structured clinical examinations (OSCEs), focus groups, and questionnaires. Results Seventy-two trainers and 708 FHWs were trained in seven South Sudan states. Trainer knowledge assessments improved significantly: 62.7% to 92.0% (p < .001). Mean FHW scores on maternal OSCEs were 21.1% pretraining, 83.4% posttraining, and 61.5% 2-3 months after training (p < .001). Corresponding mean newborn OSCE scores were 41.6%, 89.8%, and 45.7% (p < .001), respectively. Questionnaires revealed high levels of use, satisfaction, and confidence. FHWs reported average 3.0 referrals (range 0-20) to healthcare facilities during 2-3 months since training, and 78.3% FHWs were more likely to refer patients. Seven focus groups showed high satisfaction with trainings, commodities, and checklists, with few barriers. Discussion As of March 2012, over 70 master trainers and over 700 FHWs have been trained in seven of the ten states in South Sudan. The success of the program depended in large part on the support of local authorities, especially the state offices of the Ministry of Health, who assisted in arranging training sites and recruiting trainers and trainees.